Development of multiple interactions mixed matrix membrane chromatography for protein fractionation in chicken egg white - Nurul Shamsinar, Shahirin (2015)
Fractionation of individual chicken egg white (CEW) proteins such as conalbumin (CNL), ovalbumin (OVL) and lysozyme (LYS) benefits the food, pharmaceuticals or nutraceuticals industry. Although packed bed chromatography is commonly used for protein separation, it still has a few limitations that need to be overcome. Membrane chromatography, which uses adsorptive membrane, is one alternative to overcome the limitation of packed bed column chromatography. Mixed matrix membrane (MMM) preparation concept provides a simple method for the preparation of membrane chromatography. In the current study, several potential low cost cation resins were screened to bind LYS at different pH. At pH 7, Lewatit CNP105 was selected for the preparation of cation exchanger MMM in the first part of study. The Lewatit CNP105 – cation exchanger MMM gave a Langmuir adsorption isotherm with the constant of 223 mg LYS/g membrane for qm and 0.045 for kd for single LYS solution. In batch binding of CEW solution at pH 7, both positively charged CEW protein (LYS, pI 10.7) and negatively charged CEW proteins (CNL, pI 6.1 and OVL, pI 4.5) were found to bind onto cation exchanger MMM. However, CNL and OVL were loosely bound and washed out during the washing step. Almost pure LYS can be recovered during the elution step of cation exchanger MMM chromatography.Multiple interactions MMM that combined Lewatit CNP105 cation resin and Lewatit MP500 anion resin, weretested to bind single protein and CEW solution in batch adsorption. In single protein experiment, the binding capacity of LYS, CNL and OVL are 52.3521 mg LYS/g membrane, 91.0453 mg CNL/g membrane and 10.8491 mg OVL/g membrane, respectively. The binding capacity of protein decreased in real CEW solution except for OVL. The reduction of the amount of protein binding might be due to the competitive binding with other impurities in CEW solution. For flow through experiment of multiple interactions MMM, three elution protocols were tested which were isocratic salt elution, linear gradient salt elution and combination of pH 3 and salt elution. Although no single protein fraction was recovered from these elution strategies tested, these fractions can be selected for further purification or used based on their targeted protein composition.